2018
DOI: 10.20469/ijbas.4.10005-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Procurement Processes on Project Execution in A Project Management Company in Cape Town, South Africa

Masithembe Kafile,
Stanley Fore

Abstract: Accentuating the compelling procurement challenges in project execution, which comprises supplier-related issues, strategy selection issues, cost reduction and savings achievement factors, data accuracy issues, and stakeholder management concerns, this study envisioned uniting the challenges that occur in procurement processes the effects these challenges have on project execution. To clearly illustrate the magnitude of challenges faced in procurement processes, a project management company in Cape Town, South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Furthermore, Vonderembse and Tracey (1999) referred to procurement as “the acquisition of goods or services, has been around for thousands of years”. In addition, Adamu et al (2021) considered procurement “as a series of activities carried out by an organization to achieve effective supply chain management.” Finally, Kafile and Fore (2018) defined procurement as “the structure that characterizes the administrative system approved by customers for the execution of project procedures and subsequent management of the project.”…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Vonderembse and Tracey (1999) referred to procurement as “the acquisition of goods or services, has been around for thousands of years”. In addition, Adamu et al (2021) considered procurement “as a series of activities carried out by an organization to achieve effective supply chain management.” Finally, Kafile and Fore (2018) defined procurement as “the structure that characterizes the administrative system approved by customers for the execution of project procedures and subsequent management of the project.”…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Other related terms in literature include acquiring/the acquisition of goods or services (the acquisition of goods and services includes the acquisition of things such as materials, equipment, supplies, utilities, repairs and maintenance and research and development) (Public Procurement and Disposal Act, 2005; Vonderembse and Tracey, 1999). It is interesting to note that while relatively classical observations of the concept, exemplified by the Public Procurement and Disposal Act (2005) and Vonderembse and Tracey (1999), may define procurement in traditional terms as the acquisition of goods or services through contractual means, contemporary authors such as Adamu et al (2021) and Kafile and Fore (2018) offer broader, more strategic interpretations. They argue that procurement encompasses not only the acquisition process but also the integration of various business operations and strategic alignment with supply chain management.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Masithembe Kafile at el. [12], characterized the main causes of poor procurement processes on project implementation into the low quality of goods delivered by suppliers, lead time variability, internal factors, poor time management, and system breakdown of online data capturing software to track supplies. Depaoli [13], in his research, indicated that procurement management is one of the most critical fields in project management that incorporates widely the administrative elements of planning, communicating organizing, staffing, leading, and controlling.…”
Section: Literature Reviewmentioning
confidence: 99%